Adapting Mathematics Curriculum Making - Evan Throop Robinson; Lori McKee (Brock University, 2024)
This paper offers insights into how mathematics education researchers can learn from preservice teachers (PSTs) by building upon parallels between adapting curriculum making and designing research. The pandemic created learning opportunities for PSTs to anticipate mathematics curriculum anew and obstacles for researchers to study their pedagogical processes. How PSTs adapted designs to include new contexts (home environment, parental/guardian involvement, materials) parallels how curriculum researchers might become more tentative, responsive, and adaptable to unforeseen circumstances.